Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 63292 by aliesam last updated on 02/Jul/19

∫_0 ^1 ∫_0 ^1  (dy/(1+y(x^2 −x))) dx

0101dy1+y(x2x)dx

Commented by mathmax by abdo last updated on 02/Jul/19

let I =∫_0 ^1  ∫_0 ^1   (dy/(1+(x^2 −x)y)) dx ⇒ I =∫_0 ^1 ( ∫_0 ^1    (dy/(1+(x^2 −x)y)))dx  ∫_0 ^1   (dy/(1+(x^2 −x)y)) = (1/(x^2 −x))ln∣1+(x^2 −x)y∣_(y=0) ^1  =(1/(x^2 −x)) ln∣x^2 −x +1∣  =((ln(x^2 −x +1))/(x^2 −x))      (because x^2 −x+1>0) ⇒  I =∫_0 ^1   ((ln(x^2 −x +1))/(x^2 −x))dx let  f(t) =∫_0 ^1    ((ln(tx^2 −x +1))/(x^2 −x))dx   with t>0  we have  f^′ (t) =∫_0 ^1   (x^2 /((x^2 −x)(tx^2 −x+1)))dx = ∫_0 ^1    (x/((x−1)(tx^2 −x+1)))dx let decompose

letI=0101dy1+(x2x)ydxI=01(01dy1+(x2x)y)dx01dy1+(x2x)y=1x2xln1+(x2x)yy=01=1x2xlnx2x+1=ln(x2x+1)x2x(becausex2x+1>0)I=01ln(x2x+1)x2xdxletf(t)=01ln(tx2x+1)x2xdxwitht>0wehavef(t)=01x2(x2x)(tx2x+1)dx=01x(x1)(tx2x+1)dxletdecompose

Commented by aliesam last updated on 02/Jul/19

nice solution sir

nicesolutionsir

Commented by mathmax by abdo last updated on 02/Jul/19

let decompose F(x)=(x/((x−1)(tx^2 −x +1)))  F(x)=(a/(x−1)) +((bx +c)/(tx^2 −x+1))  a =lim_(x→1)  (x−1)F(x) = (1/t)  lim_(x→+∞)  xF(x) =0 = a+(b/t) ⇒at +b =0 ⇒b =−at =−1 ⇒  F(x) = (1/(t(x−1))) +((−x +c)/(tx^2 −x +1))  F(2) =(2/(4t−1)) =(1/t) +((−2+c)/(4t−1)) ⇒2 =((4t−1)/t) −2 +c ⇒c=4−((4t−1)/t) =(1/t) ⇒  F(t) =(1/(t(x−1))) +((−x+(1/t))/(tx^2 −x+1)) =(1/(t(x−1))) +((−tx +1)/(t(tx^2 −x+1))) ⇒  f^′ (t) =∫_0 ^1    (1/(t(x−1)))dx −(1/t) ∫_0 ^1   ((tx−1)/(tx^2 −x+1))dx  =(1/t){∫_0 ^1   (dx/(x−1)) −(1/2)∫_0 ^1   ((2tx−1−1)/(tx^2 −x+1))dx}  =(1/t) { [ln∣x−1∣ −(1/2)ln(tx^2 −x+1)]_(x=0) ^1   +(1/2) ∫_0 ^1     (dx/(tx^2 −x+1))}  =(1/t){[  ln(((∣x−1∣)/(√(tx^2 −x+1))))]_(x=0) ^1   +(1/2) ∫_0 ^1    (dx/(tx^2 −x+1))}....perhaps the integral diverges...  ...be continued....

letdecomposeF(x)=x(x1)(tx2x+1)F(x)=ax1+bx+ctx2x+1a=limx1(x1)F(x)=1tlimx+xF(x)=0=a+btat+b=0b=at=1F(x)=1t(x1)+x+ctx2x+1F(2)=24t1=1t+2+c4t12=4t1t2+cc=44t1t=1tF(t)=1t(x1)+x+1ttx2x+1=1t(x1)+tx+1t(tx2x+1)f(t)=011t(x1)dx1t01tx1tx2x+1dx=1t{01dxx112012tx11tx2x+1dx}=1t{[lnx112ln(tx2x+1)]x=01+1201dxtx2x+1}=1t{[ln(x1tx2x+1)]x=01+1201dxtx2x+1}....perhapstheintegraldiverges......becontinued....

Commented by mathmax by abdo last updated on 02/Jul/19

let change the ordre of integral  I =∫_0 ^1 (∫_0 ^1   (dx/(1+yx^2 −yx)))dy  we have  A(y)=∫_0 ^1   (dx/(yx^2 −yx +1)) →let solve yx^2 −yx +1 =0  Δ =y^2 −4y <0  due to  0≤y≤1 ⇒yx^2 −yx +1=y(x^2 −x +(1/y))  =y( x^2 −2x(1/2) +(1/4) +(1/y) −(1/4)) =y{ (x−(1/2))^2  +((4−y)/y)}    ( y≠0)  we use the changement  x−(1/2) =(√((4−y)/y))t ⇒t =((2x−1)/2) (√(y/(4−y)))  A(y) = ∫_(−(1/2)(√(y/(4−y)))) ^((1/2)(√(y/(4−y))))      (1/(y ((4−y)/y)(1+t^2 ))) (√((4−y)/y))dt  =(1/(√(y(4−y)))) [arctan(t)]_(−(1/2)(√(y/(4−y)))) ^((1/2)(√(y/(4−y))))   =((2arctan((1/2)(√(y/(4−y)))))/(√(y(4−y)))) ⇒  I =2 ∫_0 ^1    ((arctan((1/2)(√(y/(4−y)))))/(√(y(4−y)))) dy    ....be continued....

letchangetheordreofintegralI=01(01dx1+yx2yx)dywehaveA(y)=01dxyx2yx+1letsolveyx2yx+1=0Δ=y24y<0dueto0y1yx2yx+1=y(x2x+1y)=y(x22x12+14+1y14)=y{(x12)2+4yy}(y0)weusethechangementx12=4yytt=2x12y4yA(y)=12y4y12y4y1y4yy(1+t2)4yydt=1y(4y)[arctan(t)]12y4y12y4y=2arctan(12y4y)y(4y)I=201arctan(12y4y)y(4y)dy....becontinued....

Terms of Service

Privacy Policy

Contact: info@tinkutara.com